PENERAPAN PENDEKATAN CTL MELALUI TEKNIK DISKUSI TIPE JIGSAW SEBAGAI UPAYA MENINGKATKAN AKTIFITAS DAN KEMAMPUAN PRAKTEK SISWA - Darman., Regina Ade (Jurnal EDik Informatika, 2018)
Problems Low activity and creativity of students in learning, a major issue that emerged in subjects Restaurant Service that affect the result of the practice of students.By implementing learning strategies Contextual Teaching And Learning (CTL) by discussing the type of jigsaw these problems can be solved. Pembelajarn contextual (Contextual Teaching and Learning) is the concept of learning that help teachers link between the material taught with real-world situations students and encourage students to make connections between the knowledge possessed by the application in their lives daily, involving seven major components effective learning, namely: constructivism (constructivism), ask (Questioning), find (Enquiry), learning community (learning community), modeling (modeling), and assessment (Authwntic assessment). Through discussion jigsaw type of problems low ability students to answer questions orally, revealing answers to oral questions, communicate in practice can be overcome. The main advantages jigsaw models for their opportunity to practice in a discussion group that provides a role as experts then explain the information to friends group members. Based on these characteristics allow students to absorb information, to discuss, and teach it in turn to her friend